APPLICATION OF PEER TEACHING LEARNING METHOD TO IMPROVE THE ABILITY TO READ THE QUR'AN CLASS IV AT SDN 21 SIJUNJUNG - Fitriawati, Hemnel (El -Hekam, 2020)
This study aims to determine the improvement of students' reading ability of Q.S Al-Fiil with the application of peer teaching methods in class IV SDN 21 Sijunjung. This research method is Classroom Action Research that is: "before-after" which compares the ability to read Q.S Al-Fiil students before and after the application of the "peer teaching" method. Each hypothesis cycle was tested through data on the values of 27 students through observation and documentation techniques. The data analysis technique used is qualitative and quantitative analysis. Tests carried out using paired paired sample t test with the following results: aspects of the knowledge of reading Q.S Al-Fiil obtained tcount (0.575) is greater than ttable (0.317). While the aspect of reading skills in Q.S Al-Fiil obtained tcount (0.905) is also greater than ttable (0.317). Then it can be concluded that the application of the method of peer teaching can improve the reading ability of Q.S Al-Fiil fourth grade students of SDN 21 Sijunjung